Novel Constrained Dual Mobility Hip Prosthesis to Combat Instability in Revision Total Hip Arthroplasty whilst Preserving Normal Function - Michael Jiang; Anton Lambers; Rodney Richardson (Case Reports in Orthopedics)
We present the case of a male patient with sepsis and a chronic discharging sinus in a multirevised total hip replacement. Following extensive debridement, the reimplanted hip became unstable. With the patient’s long-term desire to return to work and ride a bicycle with his children, the patient agreed to proceed with a novel, custom-designed, constrained dual mobility liner which allowed unrestricted movement. In 2017, the patient underwent revision surgery with this novel dual mobility constrained prosthesis. The patient was very quickly able to regain independence. After 16 years of unemployment, he managed to return to gainful employment as a cleaner rapidly regaining function as well as finally being able to ride a bike with his children for the first time.